HSF and Hsp Gene Families in sunflower: a comprehensive genome-wide determination survey and expression patterns under abiotic stress conditions - Ceylan, Yusuf; Altunoglu, Yasemin Celik; Horuz, Erdoğan (Springer Science and Business Media LLC, 2023)
Sunflowers belong to the Asteraceae family, which comprises nutrimental and economic oilseed plants. Heat shock proteins (Hsps) are protein families vital for all organisms' growth and survival. Besides the ordinary conditions, the expression of these proteins ascends during abiotic stress factors such as high temperature, salinity, and drought. Using bioinformatics approaches, the current study identified and analyzed HSF and Hsp gene family members in the sunflower (Helianthus annuus L.) plant. HSF, sHsp, Hsp40, Hsp60, Hsp70, Hsp90, and Hsp100 domains were analyzed in the sunflower genome, and 88, 72, 192, 52, 85, 49, and 148 genes were identified, respectively. The motif structures of the proteins in the same phylogenetic tree were similar, and the α-helical form was dominant in all the protein families except for sHsp. The estimated three-dimensional structure of 28 sHsp proteins was determined as β-sheets. Considering protein-protein interactions, the Hsp60-09 protein (38 interactions) was found to be the most interacting protein. The most orthologous gene pairs (58 genes) were identified between Hsp70 genes and Arabidopsis genes. The expression analysis of selected genes was performed under high temperature, drought, and high temperature-drought combined stress conditions in two sunflower cultivars. In stress conditions, gene expressions were upregulated for almost all genes in the first half and first hours at large. The expressions of HanHSF-45 and HanHsp70-29 genes were raised in two cultivars under high temperature and high temperature-drought combined stress conditions. This study presents a blueprint for subsequent research and delivers comprehensive knowledge of this vital protein domain.
Keywords: Hsf (Heat Shock Factors); Helianthus Annuus L; Hsp (Heat Shock Proteins); Genome-Wide Determination; Bioinformatics Analysis; Gene Expression; 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health